Lower Extremity Amputation and Mortality Rates in the Reconstructed Diabetic Charcot Foot and Ankle With External Fixation: Data Analysis of 116 Patients. Issue 2 (April 2016) - Ramanujam, Crystal L.; Han, David; Zgonis, Thomas
The aim of this study was to determine the lower extremity amputation and mortality rates of a group of patients who underwent reconstructive surgery using circular external fixation for treatment of diabetic Charcot neuroarthropathy (CN) of the foot and/or ankle. Existing studies regarding lower extremity amputation or mortality rates for diabetic CN of the foot and/or ankle have been performed on mostly conservatively treated patients. The objective of the statistical analysis in this studied population was to understand the difference in overall amputation and mortality rates between the 2 main groups: one with foot and/or ankle ulceration (group 1), and the other without ulceration or osteomyelitis (group 2, control group). Within group 1, 2 subgroups were established: one with osteomyelitis (group 1A) and the other without osteomyelitis (group 1B). Initially, a retrospective analysis of 150 consecutive surgically reconstructed diabetic foot and ankle cases using circular external fixation from January 2005 through December 2012 was conducted. Those which were not supported with the diagnosis of diabetic CN were excluded and the 2 other charts without proper follow-up duration (6 months) for analysis were removed, resulting in the final sample size of N = 116. There were a total of n = 7 (6.0%) below the knee amputations (group 1A = 1, group 1B = 4, and group 2 = 2) with a total of n = 5 mortalities (4.3%) (group 1A = 2, group 1B = 2, and group 2 = 1). The total amount of time for a lower extremity amputation event (n = 7) since the time of surgical reconstruction was 729.43 ± 519.73 days (range 230-1777 days) while for a mortality event (n = 5), it was 1302.00 ± 765.48 days (range 633-2499 days). Levels of Evidence: Prognostic, Level III: Retrospective study